(a) Use appropriate algebra and Theorem to find the given inverse Laplace transform. (Write your answer as a function of t.)
Lāˆ’1 {3s āˆ’ 10/ s2 + 25}
(b) Use the Laplace transform to solve the given initial-value problem.
y' + 3y = e6t, y(0) = 2

Respuesta :

(a) Expand the given expression as

[tex]\dfrac{3s-10}{s^2+25}=3\cdot\dfrac s{s^2+25}-2\cdot\dfrac5{s^2+25}[/tex]

You should recognize the Laplace transform of sine and cosine:

[tex]L[\cos(at)]=\dfrac s{s^2+a^2}[/tex]

[tex]L[\sin(at)]=\dfrac a{s^2+a^2}[/tex]

So we have

[tex]L^{-1}\left[\dfrac{3s-10}{s^2+25}\right]=3\cos(5t)-2\sin(5t)[/tex]

(b) Take the Laplace transform of both sides:

[tex]y'(t)+3y(t)=e^{6t}\implies (sY(s)-y(0))+3Y(s)=\dfrac1{s-6}[/tex]

Solve for [tex]Y(s)[/tex]:

[tex](s+3)Y(s)-2=\dfrac1{s-6}\implies Y(s)=\dfrac{2s-11}{(s-6)(s+3)}[/tex]

Decompose the right side into partial fractions:

[tex]\dfrac{2s-11}{(s-6)(s+3)}=\dfrac{\theta_1}{s-6}+\dfrac{\theta_2}{s+3}[/tex]

[tex]2s-11=\theta_1(s+3)+\theta_2(s-6)[/tex]

[tex]2s-11=(\theta_1+\theta_2)s+(3\theta_1-6\theta_2)[/tex]

[tex]\begin{cases}\theta_1+\theta_2=2\\3\theta_1-6\theta_2=-11\end{cases}\implies\theta_1=\dfrac19,\theta_2=\dfrac{17}9[/tex]

So we have

[tex]Y(s)=\dfrac19\cdot\dfrac1{s-6}+\dfrac{17}9\cdot\dfrac1{s+3}[/tex]

and taking the inverse transforms of both sides gives

[tex]y(t)=\dfrac19e^{6t}+\dfrac{17}9e^{-3t}[/tex]